'Oh, was that "experiential learning"?!' Spaces, synergies and surprises with Kolb's learning cycle. Issue 2 (April 2016) - Tomkins, Leah; Ulus, Eda
We share findings from empirical research into Kolb's experiential learning approach, using our reflections as teachers and data from our undergraduate management students. The experiential learning experience emerges as a space where bodies, feelings and ideas move and develop in intimate relationship with one another. This is a space where teachers exercise authority over, and commitment to, the here-and-now, risking corporeal and intellectual exposure. We probe the concept of experience in experiential learning, suggesting that teachers require a kind of 'experiential expertise' to draw both on embodied felt sense and on what one has done in one's own career to role-model the transformation of experience into knowledge, which is at the heart of Kolb's theory. We explore a blurring of experiential agency, and the tendency for students to appropriate the teacher's experience rather than dwell on or develop their own. For us, experiential learning is more usefully seen as 'relationship-centred' than 'student-centred', and we contrast this relational focus with the way experiential learning seems to have been popularised as anti-interventionist, a kind of educational 'laissez-faire'. Based on these reflections, we suggest powerful connections between phenomenology and theories of space as a way of conceptualising the complexities and richness of teaching and learning experiences.